Characterization of a Drosophila model to study functions of guarana seeds - Maria Fernanda Manica-Cattani; Ivana Beatrice Mânica da Cruz; Yukiko Sato-Miyata; Lucas Siqueira Trindade; Felipe Rogalski; Euler Esteves Ribeiro; Manabu Tsuda; Toshiro Aigaki (PLoS ONE, 2025)
The seeds of the Amazonian fruit, guarana (Paullinia cupana), have been used as traditional medicine and, in recent years, as an ingredient in commercial energy beverages. However, mechanisms underlying the beneficial effects of guarana are not well understood. To establish a model system to study molecular mechanisms underlying the beneficial effects of guarana, we investigated how its ingestion affects physiology in the fruit fly, Drosophila melanogaster. We found that guarana enhanced oxidative stress resistance, longevity, physical activity, and fecundity of flies. To deepen our understanding of guarana function, we performed transcriptomic, metabolomic, and fecal microbiome analyses. Transcriptomic analysis identified 58 upregulated and eight downregulated genes in guarana-fed flies. Highly upregulated genes included those encoding detoxification enzymes, such as cytochromes P450 (CYPs), glutathione S-transferases (GSTs), and Juvenile hormone epoxide hydrolase 1 (Jheh1). Metabolomic analysis identified glutathione metabolism, an antioxidant system, as being promoted by guarana ingestion. These findings likely represent the molecular basis for enhanced oxidative stress resistance and longevity in guarana-fed flies. We also analyzed fecal microbiota composition and found significant changes: guarana increased the proportion of probiotic Lactobacillus species, some species known to extend longevity. At the same time, it decreased the proportion of Enterococcus faecalis, a species known to reduce longevity. These changes might have contributed to the beneficial effects of dietary guarana. Thus, we demonstrate that guarana exerts beneficial effects in flies and provide fundamental data for further investigation of its biological mechanisms in Drosophila.